The effectiveness of warm ginger compresses in reducing back pain among third trimester pregnant women at Arinda Clinic, Palembang City - Handayani, Tri Restu; Contesa, Lina (Institute Of Computer Science (IOCS), 2026)
This study aimed to determine the effectiveness of warm ginger compresses in reducing back pain among third-trimester pregnant women. A quasi-experimental study with a one-group pretest–posttest design was conducted at Arinda Clinic, Palembang. A total of 46 third-trimester pregnant women experiencing mild to moderate low back pain were selected using purposive sampling. The intervention consisted of warm ginger compress application for 15–20 minutes per session, three times per week for two weeks. Pain intensity was measured using the Visual Analog Scale before and after the intervention. Data were analyzed using the Wilcoxon test. The results showed a significant decrease in back pain intensity after the intervention. Before treatment, most respondents experienced moderate pain, while after the intervention, most experienced mild pain and several respondents reported no pain at all. Statistical analysis indicated a significant difference between pretest and posttest pain scores (p < 0.05). In conclusion, warm ginger compress therapy is effective in reducing back pain intensity in third-trimester pregnant women and can be recommended as a safe and low-cost complementary non-pharmacological intervention in maternity care.